Plan de Manejo en el centro de rescate paseo “Los Monos”, cantón Pastaza, provincia de Pastaza - Jaya Guanoluisa, Ana Belén (2015)
This research proposes the development of a management plan for rescue walk center "Monkeys" Canton Pastaza province of Pastaza. The management plan becomes a tool for planning, management and control of the activities carried out in-situ in order to preserve the area and species long term maintaining environmental balance. The first chapter consists of the legal aspect and analysis of descriptive technical diagnosis, identifying the socio economic, cultural and environmental facts plus the FODA matrix was developed with the cooperation of the people involved, identifying factors inside and outside the site, aligning planning proposal. The second chapter was based on zoning divided into three areas, including restoration, conservation and buffer, in order to mitigate negative impacts on them, detailing used rules and objectives were achieved in each area….